Vegan spread applications of alternative protein from torula yeast: product development and consumer perception - Gärtner, Ann-Kristin; Matullat, Imke; Genuttis, Darleen; Engelhardt, Sarah; Sveinsdóttir, Kolbrún; Niimi, Jun; Rusu, Alexandru (Frontiers in Sustainable Food Systems, 2024)
Alternative protein sources are gaining attraction in food industry and consumers. Proteins obtained by single-cell organisms, such as torula yeast, are of enormous interest, as they are highly scalable, efficient, and sustainable, and the production costs are comparably low. Nevertheless, proteins obtained from yeasts are still mostly known and studied for feed applications, despite their nutritional, functional, and sensory benefits for various food applications. Testing consumer acceptance of products, especially products containing alternative proteins provides insights into, e.g., market success, consumer perception, and optimization potential. In this study, the development of two vegan spread powders, high in protein and containing torula yeast as an alternative protein source, is introduced. The result of food product development using torula yeast were “Leberwurst”-style (14.7% protein) and a “Balkan”-style (9.7% protein) spreads both meeting the criteria “at least 20% kcal from proteins of total product kcal” and thus claimable as “high-protein.” The application of the alternative protein from torula yeast within the final products was studied by a consumer acceptance test (n = 123) within three different countries (Germany, Iceland, and Sweden). Consumers also rated their trust in food production actors, the food industry in particular, and their willingness to try new foods. Overall, both spreads received acceptance values in the range of “like slightly.” It is noticeable that the consumers liked the spread “Balkan style” more than “Leberwurst”-style. The background variables revealed higher neophobic characteristics of Icelandic consumers compared with Swedish or German consumers. However, German consumers felt transparency, and communication was missing, but Icelandic consumers, in general, had more trust in the overall food value chain. This knowledge allows for the development of strategies that address cultural-specific barriers and capitalize on cultural values that promote openness to culinary innovation. The identification of cultural variations in consumer preferences emphasizes the need for customized approaches to product development and marketing. These findings could have implications for businesses and policymakers in understanding and catering to the preferences and concerns of consumers in these respective countries. Businesses might benefit from emphasizing transparency and improving communication strategies. This could involve providing clear information about the sourcing, production, and other aspects of the food value chain.